2012
DOI: 10.1100/2012/643904
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Toxicity of Soluble Fractions of Industrial Solid Wastes onDaphnia magnaandVibrio fischeri

Abstract: Industrial wastes may produce leachates that can contaminate the aquatic ecosystem. Toxicity testing in acute and chronic levels is essential to assess environmental risks from the soluble fractions of these wastes, since only chemical analysis may not be adequate to classify the hazard of an industrial waste. In this study, ten samples of solid wastes from textile, metal-mechanic, and pulp and paper industries were analyzed by acute and chronic toxicity tests with Daphnia magna and Vibrio fischeri. A metal-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The results for the D. magna acute and chronic tests and V. fischeri tests are summarized in Table 3, and are expressed as defined for the application in the WTox Model. Details of the results and discussion of these tests can be seen in Flohr et al, (2012a). Among the organisms exposed to samples of the textile industry, it was observed that the sample TX3 induced the highest acute toxicity values both for V. fischeri as to D. magna.…”
Section: Magna and V Fischeri Toxicity Testsmentioning
confidence: 98%
See 4 more Smart Citations
“…The results for the D. magna acute and chronic tests and V. fischeri tests are summarized in Table 3, and are expressed as defined for the application in the WTox Model. Details of the results and discussion of these tests can be seen in Flohr et al, (2012a). Among the organisms exposed to samples of the textile industry, it was observed that the sample TX3 induced the highest acute toxicity values both for V. fischeri as to D. magna.…”
Section: Magna and V Fischeri Toxicity Testsmentioning
confidence: 98%
“…Each level corresponds to a particular risk classification. For each parameter, ranges of toxicological effect were established from outcome evaluations of researches already undertaken by LABTOX team members (Matias et al, 1998a;Matias et al, 1998b;Carvalho Pinto-Silva et al, 2003Perreault et al, 2011;Melegari et al, 2012;Flohr et al, 2012a;Flohr et al, 2012b),and studies in the available literature (Lambolez et al, 1994;Villegas-Navarro et al, 1999;Knops et al, 2001;Backhaus et al, 1997;Lappaleinen et al, 2001;Ç avas and Ergene-Gozucara, 2003;Rodriguez et al, 2006;Picado et al, 2008;Kang et al, 2010;Kostamo and Kukkonen, 2003;Grinevicius et al, 2009;Ç avas and Ergene-Gözükara, 2005;Avci et al, 2005;Huang et al, 2007).…”
Section: Toxicity Levelsmentioning
confidence: 99%
See 3 more Smart Citations